Chapter First investigation of microplastic pollution in Monastir Sea surface water (eastern Tunisia) - Jaziri, Hela (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
In the framework of COMMON MED-project, a sampling campaign was carried out during December 2020 along two radials namely: T1 and T2. The findings showed that microplastic particles (MPs), ranging from 0.31 to 4.9 mm. For all samples, white color and fragments are the most common. As well, HDPE and PE are the predominant polymers. The concentrations of MPs varied between 62,095,032 and 260,979,12 items/km² with a density of 4 times greater in the T2 radial, which shows the influence of urban and marina origin on plastic contamination among seaside tourist one.